SYSTEM PERSPECTIVE OF PUBLIC GOVERNANCE - Bialynicki-Birula, Pawel (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
Steering social processes becomes more and more problematic, which implies the necessity to seek new, more sophisticated methods of public policy and forms of social coordination. The condition for their development and then their effective implementation is to learn nature and logic of action of complex social systems, the objective that can largely be met by using system approach.The paper concerns possibilities to use virtues of thinking in system categories for conceptualization and projection of actions in public sphere. Reflection on the social complexity phenomenon and determinants of system approach application as a method to reduce such complexity, in order to capture the logics of social systems, represents a starting point. Key research issue is represented by deliberations on public governance expressed as steering complex social systems. A lot of effort has been devoted to self-organization phenomenon while making use of the scientific outputs of cybernetics and macrosociology. The conclusion is that in the conditions of complexity and high dynamics of processes, the efficacy of public governance depends on the abilities to use endogenic potentials of social systems.Redefinition of government role in public authority area should be aimed at, through giving up top-down and narrowly defined interventions for exercising general supervision and active leadership. Thus soft forms of coordination should be opted for, such as soft law, with the possibility of further, ex post, specification of public policy goals, modelled after standards of contractual relationships. Public actions should have inclusive character, and the goals defined should be an outcome of public debate.